Bioinspired by both mussel foot protein and bone sialoprotein: universal adhesive coatings for the promotion of mineralization and osteogenic differentiation. Issue 31 (13th July 2020) - Long, Xiaoling; Xu, Huilin; Zhang, Dongyue; Li, Jianshu
Abstract : Natural protein bioinspired coatings are developed to promote the mineralization and osteogenic differentiation of MC3T3-E1 cells for implant material use. Abstract : Generally, the poor osteointegration between bone implant materials and host tissue can lead to severe implant failure, accompanied by a series of postoperative complications. One of the reliable and valid solutions for eliminating these concerns is to improve the biointerface performance of implants via various modification methods. Although some progress has been achieved in recent decades, it still remains a great challenge and requirement to develop a facile and universal method for the implant modification of various materials. In this work, bioinspired by the physiological functions in osteoanagenesis of bone sialoprotein (glutamic acid-rich protein), a series of bi-functional polymers were elaborately designed and synthesized through the reversible addition–fragmentation chain transfer (RAFT) polymerization of methacryloylamido glutamic acid (MGlu) and dopamine methacrylamide (DMA ). Due to the abundant catechol pendants of the polymer chains, these functional polymers are able to form stable coatings on the surfaces of various substrates via only an environmentally friendly and mild spin-coating process. Furthermore, the results of mineralization experiments in vitro clearly indicated that these functional polymeric coatings on titanium plates have the capability to effectively promote mineral deposition. In particular, polymeric coatings composed with a nearly equal monomer composition (1.0/1.2) could induce the formation of calcium phosphate (CaP) with a Ca/P ratio of 1.7/1, which is close to the ratio of calcium to phosphorus in natural hydroxyapatite. Moreover, all of the polymeric coatings facilitated the adhesion, spreading, proliferation, and osteogenic differentiation of MC3T3-E1 cells. These effects were directly affected by the composition of the polymer chains, especially the content of glutamic units.